A Collaborative I-LEARN Project With Kindergarten and Second-Grade Urban Teachers and Students at a University-Assisted School. (January 2021) - Lee, Vera J.; Tecce DeCarlo, Mary Jean; Grant, Allen; Neuman, Delia
This study describes an information/digital literacy project that was conducted with kindergarten and second-grade students and teachers at a university-assisted school. The study centered on the I-LEARN model—a learning model that blends research and theory from information science and instructional systems design—and investigated how the model could be used to support information-rich learning at the school; the dimensions of digital literacy that were most salient for the teachers and students; and how information/digital literacies can be taught in this setting. The data revealed that each teacher's approach to the project, their assumptions about their students' background with technology and research, and their own knowledge about information/digital literacies had significant effects on their students' learning outcomes.